Innovation, Wages, and Polarization in China - Belton M. Fleisher; William H. McGuire; Yaqin Su; Min Qiang Zhao (Institute of Labor Economics (IZA), 2018)
Using data from CHIPS 1995-2013, we find polarization of employment from middle-income Skilled jobs to work in the Unskilled and Self-Employment job categories. This redistribution of employment is consistent with the automation of routine noncognitive tasks in the skilled sector as analyzed in a number of papers on advanced economies and some work on the Chinese economy. While the Unskilled and Self-Employment jobs remain below median income, the redistribution of employment has not been associated with a commensurate polarization of labor income. We find no evidence of polarization of either employment or income at the upper end of the job-skill spectrum.
Keywords: J24; J31; O30; D33; 330; polarization; innovation; wage growth; China